2016
DOI: 10.1086/685549
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Parameters of Right Ventricular Function Predict Mortality in Acute Respiratory Distress Syndrome: A Pilot Study

Abstract: Right ventricular (RV) dysfunction in acute respiratory distress syndrome (ARDS) contributes to increased mortality. Our aim is to identify reproducible transthoracic echocardiography (TTE) parameters of RV dysfunction that can be used to predict outcomes in ARDS. We performed a retrospective single-center cohort pilot study measuring tricuspid annular plane systolic excursion (TAPSE), Tei index, RV-fractional area change (RV-FAC), pulmonary artery systolic pressure (PASP), and septal shift, reevaluated by an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 38 publications
3
23
2
1
Order By: Relevance
“…25 Likewise, the presence of PH has been associated with increased mortality in acute respiratory distress syndrome as well as chronic obstructive pulmonary disease. 26,27 In our study, we found that transfusion of RBCs is followed by a sustained increase in MPAP of 2 to 3 mm Hg relative to already-elevated pretransfusion values and to a comparator group of asanguinous fluid infusions in the same patient population. Colloid infusions elevated MPAP relative to crystalloid infusions, but not as greatly as RBCs.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…25 Likewise, the presence of PH has been associated with increased mortality in acute respiratory distress syndrome as well as chronic obstructive pulmonary disease. 26,27 In our study, we found that transfusion of RBCs is followed by a sustained increase in MPAP of 2 to 3 mm Hg relative to already-elevated pretransfusion values and to a comparator group of asanguinous fluid infusions in the same patient population. Colloid infusions elevated MPAP relative to crystalloid infusions, but not as greatly as RBCs.…”
Section: Discussionsupporting
confidence: 51%
“…In a retrospective analysis in a medical ICU, echocardiographically determined PH was found in over 40% of patients and was associated with increased mortality . Likewise, the presence of PH has been associated with increased mortality in acute respiratory distress syndrome as well as chronic obstructive pulmonary disease …”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown in the larger cohort of 38 patients that TAPSE, MPI, and septal shift correlated with ARDS severity and death, and of these indices, TAPSE was an independent predictor of mortality. 25 The data from this study expand on our pre- The following limitations are recognized in our study. As specific echocardiographic views adequate for measurement of TAPSE, MPI, and FAC were not routinely obtained at our institution before 2013 and only patients with two complete echocardiograms for comparison were included, our study size of fourteen patients was small.…”
Section: Discussionmentioning
confidence: 62%
“…We have previously shown in the larger cohort of 38 patients that TAPSE, MPI, and septal shift correlated with ARDS severity and death, and of these indices, TAPSE was an independent predictor of mortality . The data from this study expand on our previous results by showing that patients will show trends in TAPSE, MPI, and FAC toward RV dysfunction from a pre‐ARDS baseline to an acute ARDS state.…”
Section: Discussionmentioning
confidence: 99%
“…Dokazano je da je Tei indeks nepouzdan ukoliko je povišen pritisak u desnoj pretkomori (npr. infarkt desne komore), budući da u tim okolnostima dolazi do brzog izjednačavanja pritiska između desne komore i desne pretkomore, ali i ukoliko se vremenski intervali potrebni za njegovo izračunavanje mjere u okolnostima postojanja različitih R-R intervala, što se prije svega odnosi na pacijente sa atrijalnom fibrilacijom [23][24][25]. Do sada nisu objavljene studije u kojima je analiziran značaj Tei indeksa za procjenu funkcije desnog srca, te prognostički značaj ovog indeksa kod bolesnika na programu hronične HD, bez značajne sekundarne plućne hipertenzije.…”
Section: Slikaunclassified